Development of interactive multimedia-based learning media on power electronics courses through e-learning - Ulfa Isni Kurnia; K. Krismadinata; Fahmi Rizal (VOLT : Jurnal Ilmiah Pendidikan Teknik Elektro, 2019)
This research aims to develop interactive multimedia-based learning media that can improve student understanding of the material DC-DC converters and AC-AC converter. The methods used to research and development with the Instructional Development Institute (IDI) model. The subject of the study was a student of electrical engineering education. Data-collecting instruments in the form of a questionnaire. Analytical techniques descriptive data to describe the validity, practicalities, and effectiveness of interactive multimedia-based learning media. The results of this study indicate that interactive multimedia-based learning media on subjects of electronics material power DC-DC converter and AC-AC converter is valid, practical, and effective.